Fatigue sensation and gene expression in trained cyclists following a 40 km time trial in the heat - VanHaitsma, T. A.; Light, A. R.; Light, K. C.; Hughen, R. W.; Yenchik, S.; White, A. T. (European Journal of Applied Physiology, 2016)
Purpose: We examined the effect of race-effort cycling exercise with and without heat stress on post-exercise perceptions of fatigue and pain, as well as mRNA expression in genes related to exercise responses. Methods: Trained cyclists (n = 20) completed 40 km time trials during temperate (TC, 21 °C) and hot (HC, 35 °C) conditions. Blood lactates were measured 1 and 5 min post-exercise. Venous blood samples and ratings of fatigue and pain perceptions were obtained at baseline and at 0.5, 8, 24, and 48 h post-exercise. Leukocyte mRNA expression was performed for metabolite detecting, adrenergic, monoamine, and immune receptors using qPCR. Results: Significantly lower mean power (157 ± 32.3 vs 187 ± 40 W) and lactates (6.4 ± 1.7 vs 8.8 ± 3.2 and 4.2 ± 1.5 vs 6.6 ± 2.7 mmol/L at 1- and 5-min post-exercise) were observed for HC versus TC, respectively (p < 0.05). Increases (p < 0.05) in physical fatigue and pain perception during TTs did not differ between TC and HC (p > 0.30). Both trials resulted in significant post-exercise decreases in metabolite detecting receptors ASIC3, P2X4, TRPV1, and TRPV4; increases in adrenergic receptors a2a, a2c, and ß1; decreases in adrenergic ß2, the immune receptor TLR4, and dopamine (DRD4); and increases in serotonin (HTR1D) and IL-10 (p < 0.05). Post-exercise IL-6 differed between TC and HC, with significantly greater increases observed following HC (p < 0.05). Conclusions: Both TT performances appeared to be regulated around a specific sensory perception of fatigue and pain. Heat stress may have compensated for lower lactate during HC, thereby matching changes in metabolite detecting and other mRNAs across conditions.